1992
DOI: 10.1182/blood.v80.12.3009.bloodjournal80123009
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human stem cell factor stimulates differentiation of mast cells from dispersed human fetal liver cells

Abstract: We have previously shown the development in vitro of tryptase+ human mast cells from fetal liver cells cocultured with murine 3T3 fibroblasts. In this study, recombinant human stem cell factor (rhuSCF), the ligand for the c-kit proto-oncogene product called Kit, stimulated the growth and differentiation primarily of mast cells from dispersed fetal liver cells, whereas recombinant human interleukin-3 (rhuIL-3) stimulated the differentiation of basophils along with other cell types. Cultures of fetal liver cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 0 publications
1
45
0
1
Order By: Relevance
“…5 and Table 1. In all culture conditions, tryptase-positive cells increased in parallel to those stained metachromatically with toluidine blue (data not shown) as reported previously [12,15,27]. After 1 week of culture, no chymase-positive cells were detected with the mAb against chymase and less than 5% of the cells were labelled with the rabbit pAb against chymase, regardless of the added cytokine mixture, while about half of the cells already were tryptase-positive and metachromatic.…”
Section: Rhil-6 Reduces Apoptosis Of Fetal Liver-derived Human Mast Csupporting
confidence: 87%
See 1 more Smart Citation
“…5 and Table 1. In all culture conditions, tryptase-positive cells increased in parallel to those stained metachromatically with toluidine blue (data not shown) as reported previously [12,15,27]. After 1 week of culture, no chymase-positive cells were detected with the mAb against chymase and less than 5% of the cells were labelled with the rabbit pAb against chymase, regardless of the added cytokine mixture, while about half of the cells already were tryptase-positive and metachromatic.…”
Section: Rhil-6 Reduces Apoptosis Of Fetal Liver-derived Human Mast Csupporting
confidence: 87%
“…Stem cell factor (SCF), which is constitutively expressed by fibroblasts and other cell types, is the ligand for Kit [5±8], and the only growth factor that by itself supports the growth and differentiation in vitro of human mast cells from haematopoietic precursors in bone marrow and peripheral blood placed into suspension cultures [9], cord blood [10,11] and fetal liver [12]. The MC T phenotype appears to predominate when protease expression is examined in such in vitro-derived mast cells by immunocytochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…However, c-kit is also involved in the regulation of growth of normal and neoplastic MC. Thus, SCF, the ligand of c-kit, induces differentiation of human MC from their progenitor cells (Irani et al, 1992;Valent et al, 1992;Kirshenbaum et al, 1992;Mitsui et al, 1993). Moreover, functional defects in the SCF or c-kit gene in mice are associated with an 'MCdeficient' phenotype (Kitamura et al, 1989).…”
mentioning
confidence: 99%
“…The studies on stem cell factor in the murine system opened the way to human primary mast cell cultures. In fact, in recent years SCF was shown to be a major growth and differentiation factor for human mast cell progenitors in cord blood mononuclear cells [17], bone marrow [18,19] and fetal liver [20]. However, in order to fully obtain differentiated human mast cells, co-culture with murine skin fibroblasts [21] or additional growth factors (IL-6, prostaglandin E 2 ) [22] may be needed.…”
Section: Mast Cell Cultures: From the Mouse To The Manmentioning
confidence: 99%
“…IL-3 does not bind to human lung mast cells [23], although it may support SCF-induced human mast cell differentiation [18,20], acting probably on SCF-responsive progenitors [24]. Recently it has been reported that IL-3 prolongs the survival of cultured human mast cells that appear to bear receptors for this cytokine [25].…”
Section: Mast Cell Cultures: From the Mouse To The Manmentioning
confidence: 99%